LONGITUDINAL PATTERNS OF BENTHIC MACROINVERTEBRATE FAUNA IN RIVER DHASAN, CENTRAL INDIA (Applied Biological Research, 2023)
This study reveals the distributional patterns and relationship of benthic  macroinvertebrate assemblages to their environments in a lesser known  river Dhasan (a tributary of river Bentwa) of Central India. Extensive  sampling was done (20 quadrates per station) in winter season (December  2018 to February 2019). The total mean density of river decreased from S1  to S4 (except S2) and differed significantly among the stations. A total of 15  (family) were observed among all the stations. Among these, Caenidae  was most abundant taxon at S1 while Thiaridae was abundant from S2 to  S4. The assemblages forming taxa varied from S1 to S4. Longitudinally, the  abundance ofCaenidae and Viviparidae declined from S1 to S4, but  Chironomidae and Gomphidae increased from S1 to S4. Similarly, the  abundance of Tabanidae and Thiaridae also increased from S1 to S4, but  decline at S3. Canonical correspondence analysis indicated current velocity  as the most important variable for faunal distribution. Functionally, the  river was separated in two zones; heterotrophic (S1 to S3) to autotrophic  S4). The abundance of collectors and gathers resulted in heterotrophic  condition while scrappers for autotrophic condition. Hence, two ecological  zones are evident in the river Dhasan.
Keywords: Caenidae; CCA ordination; Peninsular plateau; river continuum concept; thiaridae; trophic status